Challenges of Family Fragility Among Muallaf An Analysis of Religious Court Decisions in Indonesia - Salma, Salma; Jarudin, Jarudin (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2025)
The marriage between individuals of different religions continues to emerge in Indonesia. Some of them convert to Islam (become Muslim) in order to have their marriage officially registered at the Religious Affairs Office (KUA), making their marriage valid. However, the reality of living a married life based on religious differences before marriage is at risk due to various crucial factors that the couple already faced prior to converting to Islam. This study aims to further elaborate on the fragility of the families of converts through an analysis of court rulings from Indonesian Religious Courts. These rulings are analyzed based on the reasons for divorce in cases from various Religious Courts, examining the judges' legal considerations and analyzing their decisions from the perspective of interfaith marriages. This normative legal research uses secondary data, consisting of primary legal materials from the rulings of Religious Courts obtained from the Supreme Court's decision directory. Additionally, secondary legal materials such as fiqh books, marriage regulations, and other related articles are also used. The findings of the study indicate that divorces occurring in these thousands of rulings were caused by non-Muslim partners reverting to their previous religion (apostasy). In these cases, judges granted divorce petitions due to the conversion from Islam to another religion (apostasy), which became one of the grounds for marriage dissolution (fasakh). From this perspective, it can be concluded that the fundamental principle in Indonesian marriage regulations, which only accepts marriages between individuals of the same religion, is aimed at ensuring the creation of intact, strong, and solid families, built on a foundation of the same religion from before marriage.